2003
DOI: 10.1046/j.1365-2958.2003.03601.x
|View full text |Cite
|
Sign up to set email alerts
|

RcsCDB His‐Asp phosphorelay system negatively regulates the flhDC operon in Escherichia coli

Abstract: SummaryThe genes involved in flagellum synthesis, motility and chemotaxis in Escherichia coli are expressed in a hierarchical fashion. At the top of the hierarchy lies the master regulator FlhDC, required for the expression of the whole set of genes. The operon flhDC is controlled by numerous regulators including H-NS, CRP, EnvZ/OmpR, QseBC and LrhA. In the present work, we report that the flhDC operon is also negatively regulated by the His-Asp phosphorelay system RcsCDB. The regulation is potentiated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
256
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(276 citation statements)
references
References 45 publications
16
256
0
Order By: Relevance
“…Active RcsB represses the expression of the class I regulator of flagella biogenesis (FlhD 2 C 2 ) by binding to the promoter region of the flhDC operon, and motility was shown to be important for biofilm formation (Francez-Charlot et al, 2003;Pratt & Kolter, 1998). Using an flhD-lacZ fusion, we observed a clear correlation between strains that are deficient in biofilm formation and strains for which flhD is repressed ( Supplementary Fig.…”
Section: Mutations In Rcsc and Rcsd Affect Biofilm Formationmentioning
confidence: 85%
See 1 more Smart Citation
“…Active RcsB represses the expression of the class I regulator of flagella biogenesis (FlhD 2 C 2 ) by binding to the promoter region of the flhDC operon, and motility was shown to be important for biofilm formation (Francez-Charlot et al, 2003;Pratt & Kolter, 1998). Using an flhD-lacZ fusion, we observed a clear correlation between strains that are deficient in biofilm formation and strains for which flhD is repressed ( Supplementary Fig.…”
Section: Mutations In Rcsc and Rcsd Affect Biofilm Formationmentioning
confidence: 85%
“…As the expression of colanic acid is required for the maturation of biofilms formed by E. coli, this suggests a positive role for the Rcs phosphorelay in the regulation of biofilm maturation (Danese et al, 2000b). On the other hand, activation of the Rcs phosphorelay has been shown to repress the expression of genes encoding surface adhesins, such as antigen 43 (Ag43) and curli, and it has been reported that overproduction of RcsB (a situation that mimics the activation of the Rcs phosphorelay) inhibits the expression of the flhDC operon, encoding the master regulators of flagella biosynthesis (Ferrières & Clarke, 2003;Francez-Charlot et al, 2003;Vianney et al, 2005). Therefore, the activation of the Rcs phosphorelay would be expected to have a negative effect on the attachment of cells to a surface.…”
Section: Introductionmentioning
confidence: 99%
“…Two decades later, this regulatory system has been shown to play roles in other physiological processes such as the regulation of the cell division genes ftsA and ftsZ (Carballès et al, 1999), the modulation of swarming (Takeda et al, 2001), and the control of flagella production (Francez-Charlot et al, 2003). In S. enterica serovar Typhi, the RcsB/C system modulates the expression of Vi antigen, flagellin and invasion proteins (Arricau et al, 1998;Houng et al, 1992;Virlogeux et al, 1995Virlogeux et al, , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Two sets of genes whose regulation by the Rcs system is well known, both in E. coli and in S. enterica serovar Typhimurium, are colanic acid genes (Brill et al, 1988;Cano et al, 2002), and genes involved in flagella synthesis and in chemotaxis (Cano et al, 2002;Francez-Charlot et al, 2003). Control of flagella and chemotaxis is exercised through the master operon flhDC (Macnab, 1996).…”
Section: S Enterica Serovar Typhimurium Rcsc Mutants With Constitutimentioning
confidence: 99%
See 1 more Smart Citation